GEORGIA’S FUEL AND ENERGY COMPLEX AFTER INDEPENDENCE - CHOMAKHIDZE, Demur (CENTRAL ASIA AND THE CAUCASUS, 2007)
This article analyzes the development trends in Georgia’s fuel and energy complex (FEC) and its individual branches over the past 15 years. The rates and dimensions of their progress are characterized during this period of time and a brief assessment is given of how the complex operates, both in the past and during the years of independence. An analysis is carried out of individual types of energy resources. In so doing, particular attention was given to the export-import of energy resources, as well as to the degree the country’s demand for them is being satisfied by local resources.